Teachers’ Effort to Implement Cultural Education and National Character Values through PPKn in Senior High School - Hamid Darmadi (Universitas Tanjungpura, 2019)
This study is titled: Teacher's Efforts to Implement Cultural Education and National Character Values Through Learning West Kalimantan State High School Bengkayang PPKn. The problem in this study is